A prática avaliativa na produção textual escrita dos discentes nos anos iniciais do ensino fundamental - Soares, Maria Zuleide Abrantes (2014)
This study aims to describe and analyze the conceptions of a teacher‟s evaluation practices concerning text writing problems of students in Learning Cycle (corresponding to the 1st, 2nd and 3rd years, also called Literacy Cycle). For this, we consider the contributions of Marcushi (2008), Fiorin (2002), Weisz (2002) Martelota (2011), Hoffman (1999), Luckesi (1995) Perrenoud (1991), Esteban (2003) Smith (1998, 2004) Smith, (1988), Freitas (2003), Rojo (2009), and DolzSchneuwly (2004), among others. Our work supports a social interactionist approach to language, a conception of formative assessment and developed a methodological approach of qualitative research, which was conducted in a public school in João Pessoa, with a teacher who accompanies a 2nd year of the Learning Cycle class. For this survey, the following instruments were used: observation in the classroom, audio-taped interview in production practices and collected written notebooks of two students to obtain data, which were analyzed based on the proposal of PNAIC, a continuing education program launched in 2012 by the MEC for the literacy teachers of public school systems in the country. The result of the analysis shows that despite the advances in teacher‟s conception, there are still obstacles in their practice, at least as regards text writing.